2015
DOI: 10.3892/br.2015.458
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of left ventricle remodeling in spontaneously hypertensive rats by valsartan is associated with the inhibition of caspase-3, -8 and -9 activities

Abstract: Abstract. The development of hypertension is closely associated with cardiac hypertrophy and apoptosis, and caspase-3, -8 and -9 are key enzymes of apoptosis. The aim of the present study was to evaluate the effects of valsartan on left ventricle hypertrophy and myocardial apoptosis in spontaneously hypertensive rats (SHRs) and to explore the mechanisms for valsartan against apoptosis. A total of 15 SHRs (16 weeks old) were randomly divided into two groups. The SHRs in the valsartan (n=8) and SHR groups (n=7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
4
1
3
Order By: Relevance
“…Caspase-8 participates in cell apoptosis through forming a death-inducing signaling complex (25). The caspase protease family occupies the central role in the apoptosis process and participates directly in early initiation, signal transmission and late apoptotic effects (26). Caspase-8 is at the peak of the cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8 participates in cell apoptosis through forming a death-inducing signaling complex (25). The caspase protease family occupies the central role in the apoptosis process and participates directly in early initiation, signal transmission and late apoptotic effects (26). Caspase-8 is at the peak of the cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Еще в одной экспериментальной работе [26] [26][27][28] доказано, что АГ ассоциируется с апоптозом кардиомиоцитов, на фоне которого в последующем развивается фиброз миокарда и повышение его жесткости. Каспазы же играют ключевую роль в апоптозе и процессах воспаления, и, тем самым, являются их маркерами.…”
Section: результатыunclassified
“…Experimental studies have demonstrated that LVRR is dictated by decreases in extracellular matrix gene expression and the decreased activities of caspase −3, −8 and −9, and the inhibition of myocardial apoptosis coupled with a significant increase in calcium handling proteins and adenylate cyclase gene expression. [19] Another important therapeutic option might be the correction of FMR. Hence, the introduction of novel device therapy, such as Mitraclip, could contribute to improve the outcomes of DCM patients.…”
Section: Left Ventricular Reverse Remodeling: the Concept Of Dynamic mentioning
confidence: 99%